Third-Party Binding of Prenuptial Deeds After Decision 69/PUU-XIII/2015 - Ade Furota Husna; Abdul Rachmad Budiono; KRA MJ Widijatmoko (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study examines the legal meaning of the phrase "...approved by the marriage registrar or notary" in Article 29 paragraph (1) of Law Number 1 of 1974 on Marriage following the Constitutional Court Decision Number 69/PUU-XIII/2015, and analyzes the binding force of notarial deeds of marriage agreements against third parties. The research employs a doctrinal legal research method through library research, utilizing statute and conceptual approaches, with primary legal materials including the Civil Code, Marriage Law, Notary Position Law, and the Constitutional Court decision, supplemented by secondary materials such as legal literature, journals, and court rulings, analyzed descriptively and prescriptively via systematic and grammatical interpretation. Findings reveal that "approval" by a marriage registrar (Civil Registry Office) or notary constitutes a formal administrative act fulfilling publicity principles, where notaries achieve this through authentic deeds, notarization, legalization, or waarmerking of private documents, inherently providing perfect evidentiary power under Article 1868 and 1870 of the Civil Code without requiring subsequent registration. However, inconsistencies arise from implementing regulations like Circulars from the Directorate General of Civil Administration and Islamic Guidance, which mandate reporting to registrars, creating norm conflicts and judicial inconsistencies as seen in rulings such as High Court Decision 50/Pdt/2021/PT SMG (recognizing validity) versus Batam Religious Court 1718/Pdt.G/2021/PA.BTM (denying binding effect). The notarial deed possesses full binding force against third parties upon approval, grounded in progressive law theory prioritizing substantive justice, legal certainty, and preventive protection, though enhanced publicity via AHU Online registration is recommended to resolve practical ambiguities and ensure uniform enforcement.